Variabilidade espacial do fósforo e das frações granulométricas de um Latossolo Vermelho Amarelo1 - Silva, Samuel De Assis; Lima, Julião Soares De Souza; Souza, Gustavo Soares De; Oliveira, Rone Batista De [UNESP]; Silva, Alessandra Fagioli Da [UNESP] (Universidade Federal do Ceará, 2010)
This study was conducted to study the spatial variability of phosphorus, estimating it through cokriging taking as covariables the size fractions of soil. The study was conducted at the experimental farm INCAPER-ES. The soil was sampled in the canopy projection of culture and depth of 0-0.20 meters in an irregular mesh with 109 points. The data were initially submitted to a descriptive analysis and correlation. Through geostatistics was made the adjustment of the variograms. The P showed significant correlation with the sand and clay fractions indicating that areas with higher concentrations of clay have lower availability of this nutrient. Both fractions have equal performance as co-variable in the estimate of the levels of P in the soil.

Este trabalho foi realizado para estudar a variabilidade espacial do fósforo, estimando-a através de cokrigagem, tendo como co-variáveis as frações granulométricas do solo. O estudo foi realizado na fazenda experimental do INCAPER-ES. O solo foi amostrado na projeção da copa da cultura e na profundidade de 0-0,20 m, em uma malha irregular com 109 pontos. Os dados foram, inicialmente, submetidos a uma análise descritiva e de correlação. Por meio da geoestatística realizou-se o ajuste dos variogramas. O P apresentou correlação significativa com as frações areia e argila indicando que áreas com maiores concentrações de argila apresentam menor disponibilidade desse nutriente. Ambas as frações possuem igual eficiência como co-variável na estimativa dos níveis de P no solo.
Spatial variability of the phosphorus and granulometric fractions of a red-yellow oxisol
Keywords: Geostatistics; Soils; Match content; Oxisols; Interpolation; Geoestatística; Solos; Teor de Fósforo; Latossolos; Interpolação